Chemical synthesis and study of structural and optoelectronic properties of CdS thin films: Effect of SILAR growth cycles (JOURNAL OF ADVANCES IN PHYSICS, 2015)
CdS thin films were deposited on glass substrates by using successive ionic layer adsorption and reaction (SILAR) method at room temperature. The effect of SILAR growth cycles on structural, morphological, optical and electrical properties of the films has been studied. The thickness of the deposited film is measured by employing weight difference method. The X-ray diffraction (XRD) and field emission scanning electron microscopy (FE-SEM) studies showed that all the films exhibit polycrystalline nature and are covered well with glass substrates. The values of average crystallite size were found to be 53 nm, 58 nm, 63 nm and 71 nm corresponding to the thin films deposited with 30, 40, 50 and 60 SILAR growth cycles respectively. From the UV–VIS spectra of the deposited thin films, it was seen that both the absorption properties and energy bandgap of the films changes with increasing number of SILAR growth cycles. A decrease of electrical resistivity has been observed with increasing SILAR growth cycles.